Kecerdasan Emosional dan Spiritual dalam Pengembangan Profesionalitas Guru Pendidikan Agama Kristen - Meilani, Meilani; Fernando, Andreas (Sekolah Tinggi Teologi IKAT Jakarta, 2023)
Christian religious education teachers, as one of the leading roles in education is to form students with the character of Christ, must develop their professionalism in duty. This research aims to explain the role of emotional intelligence and spiritual intelligence in the development of professionalism of Christian religious education teachers, especially in Educational Institutions, which are schools. The research method used is descriptive qualitative, using observation and literature studies to collect data. This study concludes that PAK teachers who have emotional intelligence due to persevering in God's Word and living it will be able to convey to students that they have similar emotional intelligence and behavior change. The spiritual intelligence resulting from intimacy with God makes PAK teachers sensitive to the leadership of the Holy Spirit so that they can change and create optimal Christian religious learning situations despite facing obstacles and challenges. Thus, professional Christian religious education teachers with emotional and spiritual intelligence similar to the Lord Jesus Christ can help students achieve the Christian religious education goal of meeting God. AbstrakGuru PAK sebagai salah satu peran utama dalam dunia Pendidikan untuk membentuk anak didik berkarakter Kristus wajib mengembangkan profesionalitas dirinya dalam melakukan tugasnya. Tujuan penelitian ini untuk mendeskripsikan peranan kecerdasan emosional dan kecerdasan spiritual dalam pengembangan profesionalitas para guru Pendidikan Agama Kristen khususnya pada Lembaga Pendidikan yakni sekolah. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan menggunakan observasi dan studi Pustaka dalam mengumpulkan data. Hasil penelitian ini adalah guru PAK yang memiliki kecerdasan emosional hasil bertekun dalam Firman Tuhan dan menghidupinya maka akan mampu mengimpartasi murid-murid untuk memiliki kecerdasan emosional serupa dan perubahan perilaku. Kecerdasan spiritual yang dihasilkan dari keintiman dengan Tuhan membuat guru PAK memiliki kepekaan akan pimpinan Roh Kudus sehingga mampu mengubah dan menciptakan situasi pembelajaran PAK optimal meskipun menghadapi hambatan dan tantangan. Dengan demikian guru PAK professional yang memiliki kecerdasan emosional dan kecerdasan spiritual serupa dengan Tuhan Yesus Kristus akan mampu membawa peserta didik mencapai tujuan pembelajaran PAK yaitu berjumpa dengan Tuhan.